2015
DOI: 10.3389/fnins.2015.00088
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in feeding behavior in rats: the relationship with neuronal activation in the hypothalamus

Abstract: There is general agreement that the central nervous system in rodents differs between sexes due to the presence of gonadal steroid hormone during differentiation. Sex differences in feeding seem to occur among species, and responses to fasting (i.e., starvation), gonadal steroids (i.e., testosterone and estradiol), and diet (i.e., western-style diet) vary significantly between sexes. The hypothalamus is the center for controlling feeding behavior. We examined the activation of feeding-related peptides in neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 100 publications
(113 reference statements)
3
32
0
1
Order By: Relevance
“…Therefore, males may have a higher propensity to expose themselves to risk in return for a reward [22]; in the case of the present study, risk of exposure in an unfamiliar environment and a reward of access to food. Male rodents are generally larger than females [36,50], therefore, they may also have a higher food intake potential [53], as was observed in the present study. Overall, the defensive behavior concealing was higher for females, which indicates that in response to a novel, unfamiliar situation females exercised more caution.…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, males may have a higher propensity to expose themselves to risk in return for a reward [22]; in the case of the present study, risk of exposure in an unfamiliar environment and a reward of access to food. Male rodents are generally larger than females [36,50], therefore, they may also have a higher food intake potential [53], as was observed in the present study. Overall, the defensive behavior concealing was higher for females, which indicates that in response to a novel, unfamiliar situation females exercised more caution.…”
Section: Discussionsupporting
confidence: 70%
“…Indeed, the analysis of non reproductive behavior of several mammalian species show sex differences in infant play, aggression, learning, exploration, activity level, behavioral circadian rythms, food intake and preference, novelty seeking, impulsivity, emotional behavior, cognitive ability and many more (Archer, 1975;Brain et al, 1991;Palanza, 2001;Alexander and Hines, 2002;Dalla and Shors, 2009;ter Horst et al, 2012;Lonsdorf et al, 2014;Argue and McCarthy, 2015;Krizo and Mintz, 2014;Fukushima et al, 2015;Carroll and Smethells, 2015) However, sex differences are not identical across species, as they depends upon specific, socio-ecological selective pressures that had acted during evolution. For example in laboratory rats and mice, females are more active and less anxious in several tests than males, but such a sex difference varies depending upon context, strain and age (Johnson and File, 1991;Palanza et al, 2001;An et al, 2011;ter Horst et al, 2012;Gioiosa et al, 2007Gioiosa et al, , 2013, while in other species of rodents, such as meadow voles, males are more active than females (Perrot-Sinal et al, 2000).…”
mentioning
confidence: 99%
“…Furthermore, to better understand these results more studies evaluating a larger rodent population considering longer study duration, more generations and the effect of gender should be performed. Indeed, the latter (effect of gender) should be specially considered since although reports indicate that gender does not affect the gut microbiota (Lay et al, 2005), other authors have reported that gender affect gut microbiota, metabolism and neural system (Bridgewater et al, 2017;Bullock, Gemzik, Johnson, Thomast, & Parkinson, 1991;Czerniak, 2001;Fukuno, Nagai, Horii, Yamamoto, & Konishi, 2018;Fukushima et al, 2015;Jasarevic´, Morrison, & Bale, 2016;Org et al, 2016), suggesting that compounds may undergo gender-dependent metabolism.…”
Section: Discussionmentioning
confidence: 99%